Oxidation of amino acids by chlorpromazine cation radical and co-catalysis by chlorpromazine - Ximenes, Valdecir Farias [UNESP]; Quaggio, Giovana Brino [UNESP]; Graciane, Fernanda Silva [UNESP]; Menezes, Manoel Lima de [UNESP] (SciRes, 2012)
The long-tem use of chlorpromazine (CPZ) may cause severe side effects. This property of CPZ might be related to pro-oxidant effects of the chlorpromazine cation radical (CPZ•+), which can be easily generated by catalytic action of peroxidases, including the neutrophil myeloperoxidase (MPO) and by methemoglobin. Aiming the comprehension of a putative physiological effect of CPZ•+ upon biomolecules, in this work we studied the reactivity of CPZ•+ with amino acids and the co-catalytic effect of CPZ during the oxidation of amino acids by horseradish peroxidase (HRP)/H2O2 system. We also studied whether natural blood plasma components as ascorbic acid, uric acid and nitrite could inhibit the oxidative effect of CPZ•+. We found that tryptophan, tyrosine and cysteine were easily oxidized by pure CPZ•+. Other amino acids as methionine, glycine, phenylalanine, aspartic acid and lysine were unreactive. The decomposition of CPZ•+ was exacerbated by uric acid, ascorbic acid and nitrite, provoking inhibition in the amino acids oxidation. In experiments with HRP/H2O2, and using CPZ as a co-catalyst, a strong effect upon oxidation of tryptophan, tyrosine and cysteine was obtained. It was also found that tryptophan was more reactive than tyrosine with CPZ•+, a feature that could be related to the recently described favorable interaction between tryptophan and CPZ. The use of CPZ as a co-catalyst is discussed regarding its role in the efficient oxidation of tryptophan.
Keywords: Tryptophan; Tyrosine; Nitrite; Chlorpromazine; Horseradish peroxidase